TEACHING READING BY USING GIST STRATEGY VIEWED FROM THE STUDENTSâ COGNITIVE ASPECT ON THE EXTENSIVE LEVEL OF ENGLISH DEPARTMENT STUDENTS IKIP PGRI MADIUN - Ningsih, Nuri Ati; Kurniawan, Arri (English Teaching Journal, 2015)
This research aimed at (1) describing the implementation of GIST strategy in the process of teaching reading viewed from the cognitif aspect having by the students; (2) finding the positif aspects of the implementation of GIST strategy; (3) knowing the weaknesses of the implementation of GIST strategy in the process of teaching reading viewed from the cognitive aspect. The method in this research was descriptive qualitative. In doing the research, there were some steps to be implemented to collect the data. They were observation, interview, and documentation. Then, analyzing data was done by reducing the data, presenting the data and drawing conclusion or verification.Â Â Â Â Â Â Â Â Â Â Â The result of the research showed that (1) GIST has been implemented maximally by the lecture based on the characteristics of this teaching strategy. To dig up the studentsâ cognitive aspects, the lecture provide the specific worksheet which represents the studentsâ cognitive level for higher order thinking skill, (2) GIST creates the studentsâ character in a good manner, such as; active, responsible and confident.They also learn how to work in a team; (3) Some weaknesses found in this research are; It needs a long time to create the instrumentÂ to supportÂ the implementation of GIST and Evaluation must be done by combining both cognitif level andÂ the level of reading ability.